Knowledge, attitude and practices related to tuberculosis among students in a public university in East Coast Malaysia - Mohd Izham, Mira Nadiah; A. Rahman, Nor Azlina; Haque, Mainul (Wolters Kluwer - Medknow, 2022)
Introduction: Tuberculosis (TB), better known as TB, is one of the infectious diseases that can cause death and therefore gains major public concerns worldwide. This study attempts to assess the knowledge, attitude and practice (KAP) related to TB among the students in a public university and find the association between the KAP with demographic factors and between the KAP themselves. Materials and Methods: Self‑administered questionnaires were distributed to 200 students from the six faculties in the university for the data collection and analysis in this cross‑sectional study. The questionnaire was divided into four parts: Demographic characteristics, knowledge, and attitude toward TB, and practices toward the prevention and control of TB. Results: The findings showed that most students had a moderate level of knowledge (obtained 47–92 out of the total 138 marks) and practice (obtained 29–57 out of the total 86 marks) and a good attitude related to TB (obtained 20–28 out of the total 28 marks). There were no significant differences in the level of KAP scores between the different genders, ages and years of study among the participants. However, a significant result was found between the KAP level of the various faculties (P < 0.001, <0.001 and 0.027, respectively), with the students from the Faculty of Medicine having the highest KAP level compared to others. Conclusion: This study also portrayed that higher knowledge was associated with a higher attitude and practice towards TB (P < 0.001 and 0.045, respectively). Based on the findings, the study proposes more health education programs to promote the awareness on early prevention of TB to achieve an improved level of KAP in controlling and preventing TB infection.